Segmentierte Rotoren in leistungsstarken Hybridantrieben - Albrecht, Thomas; Hubert, Markus; Franke, Jörg; König, Werner (Antriebstechnik, 2013)

The development and validation of a segmented rotor design for electric motors in hybrid vehicle applications - Franke, Jörg; Albrecht, Thomas; Lamprecht, Erik; Hubert, Markus; Schneider, Michael (2014 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2014, 2014)
This paper presents investigations into the development and validation of a new segmented rotor design. A segmented rotor design avoids the significant waste of the precious electric steel material and therefore leads to cost reductions. For validation of the segmented rotor design, a finite element method simulation, tensile tests, centrifugal stress tests and iron loss measurements were carried out. The simulation results allow for determining of a segmented rotor design. The tensile and centrifugal test results further confirm the capability of the segmented rotor design for serial applications. The results confirm that the rotor design does not generate additional iron losses. © 2014 IEEE.
Keywords: electric mobility; iron losses; manufacturing processes; rotor segmentation